Continuous Skin Rejuvenation by Combining Nonablative Fractional Laser With Daily Application of a Multibeneficial Composition Formulation: A Blinded Randomized Clinical Trial Study - Xinxuan Zhang; Manru Ning; Mengqing Lin; Qi Tang; Yihuai Liang; Feifei Wang; Xiaoke Xu (Health Science Reports)
ABSTRACT Background and Aims Skin aging is a common concern among individuals, and laser treatments are recognized as one of the most effective approaches to mitigate the aging process. The study aims to compare a multibeneficial formula serum versus a blank formulation in achieving maximum efficacy following a single treatment of nonablative fractional laser for facial skin rejuvenation. Methods This study was a double‐blind, split‐face, monocentric, randomized clinical trial in China (September 24, 2023–March 07, 2024), and 37 patients seeking the Fotona 4D laser treatment for aging‐related facial changes were enrolled. After one full‐face laser treatment, each patient applied the test serum to one side and the blank formulation to the other, randomly, twice daily for 28 days. Two dermatologists assessed facial skin quality and aging signs at baseline and Day 0 (D0, immediately after the laser treatment), D3, D7, D14, and D28. Noninvasive measurement and self‐assessment questionnaires were also administered at each visit. According to the types of variables, appropriate statistical tests, including the Friedman test, ANOVA test, and Wilcoxon signed‐rank test, were used to examine the within‐groups or between‐groups differences. Results Thirty‐three women, aged 35–49 years, completed the study. After 28 days of the test serum application, the visual clinical scores rated by investigators showed more significantly beneficial changes on the test side than those on the control. More significant improvements in index parameters for the test sides were also found both in wrinkles with a 21.14% decrease of SEw value from the baseline and in elasticity with a 14.99% decrease of R2 value, while the corresponding reductions were 3.83% for SEw and 4.10% for R2 found on the control sides. The reduction of the nasolabial folds area proportion, analyzed by Primos, was 10.61% on the test sides and 3.39% on the control. No adverse events were reported. Conclusion The serum with a multi‐beneficial composition can contribute to achieving a more significant and sustainable efficacy after the Fotona 4D treatment in skin rejuvenation improvement. ClinicalTrials.gov ID: NCT06140628.